Food Estate Development: Political-Economic and Legal Perspectives - Hidayaturrahman, Mohammad; Handrito , Radityo Putro; Putu Sugiantiningsih, Anak Agung; Ubaid, Ahmad Hasan; Haris, Rillia Aisyah; Suprianto, Suprianto (Indonesian Journal of Advocacy and Legal Services, 2025)
The Indonesian Government is trying to overcome the threat of a food crisis, one of which is through a food estate program. This study was conducted to answer the political-economic and legal perspectives of food estate development in Kalimantan. Researchers collected data by visiting three food estate locations in the Gunung Mas, Pulang Pisau, and Kapuas Regencies. In the field, researchers conducted observations, in-depth interviews, and focus-group discussions with many informants. After the data were collected, researchers conducted multidisciplinary analyses and studies. The results of this study showed that the Government's plan to increase food production through food estates in Central Kalimantan was not achieved. The Government's economic and political goals violate applicable laws. In this context, the law follows the wishes of political actors and economic interests. Food estates positively impact infrastructure development at food estate locations, especially in the Kapuas and Pulang Pisau Regencies. This has a positive impact on the economy. However, residents did not feel these benefits at the food estate location in the Gunung Mas Regency. The development of a food estate in Gunung Mas violates the law. Land clearing by cutting down trees in a 600-hectare forest can violate the Forestry and Forest Protection Laws. To avoid any legal violations, a breakthrough is needed in the form of a Government Regulation in place of Law (Peraturan Pemerintah Pengganti Undang-Undang/ PERPUU). This program cannot be implemented without a legal framework, such as a law that regulates the entire process from upstream to downstream. Therefore, food estates are being developed throughout rural areas in Indonesia.